1995
DOI: 10.1093/milmed/160.5.219
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of the Navy's Hearing Conservation Program

Abstract: The purposes of this study were to determine the incidence of significant threshold shift (STS) for a large number of Naval fleet personnel, evaluate hearing conservation program (HCP) compliance for a large number of Naval ships, and determine whether two currently used compliance measures are useful means of evaluating HCP effectiveness. Data were collected from 12,492 medical records of 154 ships/submarines regarding STS incidence and follow-up, percent of valid audiograms, and other HCP elements. Data anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…There are many examples of studies which have examined audiometric results in an attempt to determine the effectiveness of HCPs, including studies of longitudinal data across one (Savell & Toothman, 1987; Brink et al, 2002) or multiple (Lee-Feldstein, 1993; Dement et al, 2005) facilities within the same industry or military occupations (Wolgemuth et al, 1995; Muhr & Rosenhall, 2011)Several studies that have utilized audiometric results to analyze HCP effectiveness have found that audiometric test results do not align well with categorized noise exposures (e.g., “high” vs “low”) (Bohnker et al, 2002). Only a few studies have also evaluated quantitative noise exposures with regards to HCP performance (Savell & Toothman, 1987; Lee-Feldstein, 1993; Davies et al, 2008), and some have determined that categorized exposures are more useful than continuous quantitative estimates (Heyer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are many examples of studies which have examined audiometric results in an attempt to determine the effectiveness of HCPs, including studies of longitudinal data across one (Savell & Toothman, 1987; Brink et al, 2002) or multiple (Lee-Feldstein, 1993; Dement et al, 2005) facilities within the same industry or military occupations (Wolgemuth et al, 1995; Muhr & Rosenhall, 2011)Several studies that have utilized audiometric results to analyze HCP effectiveness have found that audiometric test results do not align well with categorized noise exposures (e.g., “high” vs “low”) (Bohnker et al, 2002). Only a few studies have also evaluated quantitative noise exposures with regards to HCP performance (Savell & Toothman, 1987; Lee-Feldstein, 1993; Davies et al, 2008), and some have determined that categorized exposures are more useful than continuous quantitative estimates (Heyer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 16% of disabling hearing loss in adults worldwide is due to occupational noise (Nelson et al, 2005). The military is one of the world's most noise hazardous occupations, and NIHL in the military continues to be an acute and costly problem despite hearing conservation programs emphasizing personal hearing protection devices (HPDs) (Bohnker et al, 2002;Wolgemuth et al, 1995). Hearing damage from acoustic trauma accounts for up to 47% of all wounded in action evacuations from Operation Iraqi Freedom and Operation Enduring Freedom and is the fourth leading reason for medical referral for combatants returning from deployment.…”
Section: Introductionmentioning
confidence: 99%
“…The ''3 dB halving rule'' which states that at 85 dBA sound intensity, exposures are limited to 8 h, and for every 3 dB increase in sound intensity, the time in noise should be reduced by half (at 100 dB intensity the occupational exposure time is limited to 15 min). Wolgemuth et al (1995) analyzed audiometric data that was collected from 12,492 medical records of 154 ships/submarines regarding significant threshold shift (STS) incidence and found an average 29% STS rate among fleet personnel of different ranks and job descriptions after one six-month exercise. As an additional hazard, there appears to be a synergistic effect of noise and jet fuel fumes, and industrial solvents causing a greater loss of hearing (Lataye et al, 2000(Lataye et al, , 2005Kaufman et al, 2005;Kim et al, 2005).…”
Section: Introductionmentioning
confidence: 99%